Medical data communication apparatus, server, medical data communication method and medical data communication program - Otsuki, Nobuhisa; Tsuchinaga, Masayoshi; Iwata, Takuya; Kito, Hodaka (2022)
A medical data communication apparatus includes a data acquisition unit configured to acquire medical data of a subject output from a medical device from the medical device, the medical device being connected for communication with the medical data communication apparatus without an external network intervening therebetween; a modification unit configured to modify the medical data based on a modification instruction received from a server, the server being connected for communication with the medical data communication apparatus through an external network, the modification instruction being for modifying specific information in the medical data; and an output unit configured to output the medical data modified by the modification unit to the external network based on a request from the server.